Pengaruh Pemberian Kurma Ajwa (Phoenix Dactylifera L) Terhadap Hasil Luaran Perinatal Pada Wanita Risiko Preeklampsia - Sello, Lenni; Mappaware, Nasrudin Andi; Aminuddin, Aminuddin; Asni, Sitti Nur; Nilawati, Andi; Latief, Shofiyah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Preeclampsia (PE) can cause disruption of fetal growth and fetal death in the womb. Preeclampsia is a major cause of maternal and infant mortality and morbidity. This study aims to analyze the effect of giving ajwa dates (Phoenix Dactylifera L) on the outcome of perinatal outcomes in women at risk of preeclampsia. This research was conducted at RSIA Sitti Khadijah 1 Makassar City, South Sulawesi Province. Sampling by purposive sampling. The study subjects consisted of 20 mothers who were given ajwa dates and 10 pregnant women who were not given ajwa dates, according to the inclusion and exclusion criteria. Characteristic data were measured using a questionnaire. To assess the results of the results using the calibration sheet and measuring instruments that have been calibrated are measured 1 time. Data analysis using Chi-Square. The results showed that the majority of samples had a high risk of hypertension (90%). Outcomes have the majority normal value in the group given the Ajwa date. BBL 76.6% had normal body weight, majority APGAR score â‰¥ 7 weeks 86.6%, and majority gestational age â‰¥ 37 weeks 90%. Giving ajwa dates has an effect on perinatal birth weight and APGAR Score. Further research needs to be done on the effect of ajwa dates on perinatal outcomes and the risk of preeclampsia on marker examinations such as soluble fms like tyrosine kinase 1 (sFlt-1).